Analysis of eye movements in the judgment of enjoyment and non-enjoyment smiles - Perron, Mélanie; Roy-Charland, Annie (Frontiers in Psychology, 2013)
Enjoyment smiles are more often associated with the simultaneous presence of the Cheek raiser and Lip corner puller action units, and these units’ activation is more often symmetric. Research on the judgment of smiles indicated that individuals are sensitive to these types of indices, but it also suggested that their ability to perceive these specific indices might be limited. The goal of the current study was to examine perceptual-attnetional processing of smiles by using eye movement recording in a smile judgement task. Participants were presented with three types of smiles: a symmetric Duchenne, a non-Duchenne and an asymmetric smile. Results revealed that the Duchenne smiles were judged happier than those with characteristics of non-enjoyment. Asymmetric smiles were also judged happier than the non-Duchenne smiles. Participants were as effective in judging the latter smiles as not really happy as they were in judging the symmetric Duchenne smiles as happy. Furthermore, they did not spend more time looking at the eyes or mouth regardless of types of smiles. While participants made more saccades between each side of the face for the asymmetric smiles than the symmetric ones, they judged the asymmetric smiles more often as really happy than not really happy. Thus, processing of these indices do not seem limited to perceptual-attentional difficulties as reflected in viewing behaviour.